Carfilzomib usage patterns and outcomes in patients with relapsed multiple myeloma: A multi‐institutional report from the Canadian Myeloma Research Group (CMRG) Database. Issue 4 (31st August 2022) - McCurdy, Arleigh; Louzada, Martha; Venner, Christopher P.; Visram, Alissa; Masih‐Khan, Esther; Kardjadj, Moustafa; Jimenez‐Zepeda, Victor H.; LeBlanc, Richard; Sebag, Michael; Song, Kevin; White, Darrell; Mian, Hira; et al.
Abstract: Carfilzomib is an active and commonly used treatment in patients with multiple myeloma (MM). Using the Canadian Myeloma Research Group Database, we performed a retrospective observational study of patients treated with carfilzomib for relapse of MM in a real‐world setting in Canada between years 2007 and 2020. A total of 445 patients were included in this study: the doublet (Kd/p, n = 218) and triplets (KCd, n = 88; KRd, n = 99; KPd/p, n = 40). One hundred and twenty‐two (27%) received carfilzomib‐based treatment in line 2, 133 (30%) in line 3, 90 (20%) in line 4, and 100 (23%) in line 5 or higher. Carfilzomib was dosed weekly in 40% of patients and twice weekly in 60%. The overall response rate of the entire cohort was 57.7%, with 33.6% of patients achieving very good partial response or better. Median progression‐free survival for the overall cohort was 6.3 months with overall survival 19.7 months. This study provides a benchmark for carfilzomib‐based regimens in the real world, demonstrating that these regimens are effective in treating patients with relapsed MM.